Lumbar sympathetic pulsed radiofrequency combined with continuous epidural infusion for treatment of painful diabetic neuropathy: A report of two cases and a literature review - Li, Shao-Jun; Feng, Dan (Journal of international medical research, 2025)
Diabetic neuropathy (DN), one of the most common late complications of diabetes mellitus, significantly affects distinct regions of the nervous system. Pain management is challenging in DN as no effective therapies exist that reverse the pathological course of DN. Several drugs are recommended as the first-line treatment for painful DN, but these are associated with various side-effects in the long term. This report presents two cases with painful DN who underwent lumbar sympathetic pulsed radiofrequency combined with continuous epidural infusion. The two cases were followed for 30 days. Lumbar sympathetic pulsed radiofrequency combined with continuous epidural infusion offered effective pain relief and improved the health-related quality of life in two patients with DN over this time period.